COMPARATIVE STUDY ON PRACTICING AND NOT PRACTICING DANCE IN INDIVIDUALS WITH DOWN SYNDROME (Fiep Bulletin - online, 2013)
Studies on the motor behavior of people with Down Syndrome - SD - there are few, presenting modest sources of help and clarification, however the term developmental delay, given the differences that can be noticed in people with motor development with SD compared with children without this syndrome is inappropriate, because it presents really are no detours and delays development. In this way, the objective of this study was to identify the benefits of dance for motor coordination in children with Down syndrome. This is a case study, descriptive exploratory quantitative field research in which two subjects were selected with SD mild to moderate and evaluating the implementation of the test motor evaluation according Rosa Neto (2002), and as the application of a model of qualitative semi-structured interview with the mother applied practitioner student of dance and a form of quantitative research for the teacher. The evaluation showed the following results: on the fine motor coordination, both young obtained 66.6%, as the overall coordination: 16.6% non-practicing and practicing dance 33.3%, as the balance is not practicing 16, 6% and practitioner 33.3%, as the body schema 50% non-practicing and practicing dance as 66.6% and the spatial organization of non-practicing practitioner 66.6 and 83.3% of participants were successful in tests
Keywords: dance; Down Syndrome; Motor Evaluation